Factors and Barriers Influencing Lean Production System Adoption in Manufacturing Industries - Chan, Shiau Wei; Ismail, Fadillah; Ahmad, M.F.; Zaman, Izzuddin; Lim, Hui Qing (ExcelingTech, 2019)
In Lean Production System (LPS), the central idea is the implementation of lean practices will reduce different types of unnecessary wastes. However, LPS implemented without an evaluation of respective organisations may lead to failure. In this study, the purpose is to identify the major factor influencing the adoption of Lean Production System and determine the major barrier that interrupts Lean Production System adoption in the manufacturing industry. The target location in this research is the manufacturing industry in Batu Pahat, Malaysia. This was a quantitative type of study and questionnaires were used to collect the data. In this study, the respondents were from the administrative level of employees. The SPSS software was used to analyse the data. The results of this research showed that the major factor influencing LPS adoption in manufacturing industry was process and the major barrier which interrupted LPS adoption was workers’ attitude or resistance. This research provided some contributions to help the manufacturing industry, especially in production department.